Tensile Strength Assessment of Palm Fruit Bunch and Corn Cob Particulates Hybrid Reinforced Aluminum-Based Composite - Chibuzo Ndubuisi Okoye; Paul Chukwulozie Okolie; Obiora Nnaemeka Ezenwa; John Chikaelo Okeke; Augustine Uzodinma Madumere; Nkechinyelu Ifeatu Ezeaku (Science: Indonesian Journal of Science, 2026)
Engineering and industrial requirements today, especially in the field of transportation, call for the development of advanced, light-weight materials with extremely high strength and performance. Recently, the increasing need to reduce energy consumption and pollution worldwide has pushed automobile industries and aerospace industries to search for lightweight materials while maintaining better performance (Kandpal et al., 2017; Mangai et al., 2023; Parveez et al., 2021). Tensile assessment of aluminium-based biocomposites containing different concentrations of palm fruit bunch (PFB) and corn cob (CCF) particles have been investigated using practical experiments. "The impact of different hybrid reinforcement concentrations on tensile performance was also studied. The biocomposites showed strong tensile properties across the various concentrations, with the highest ultimate tensile strength of 189.78 MPa achieved by the AA6063 aluminum alloy biocomposite. This strength was notably higher than that of the unreinforced alloy. Overall, the results showed that adding palm fruit bunch (PFB) and corn cob fiber (CCF) significantly enhanced the tensile strength.